Seagrasses and seagrass habitats in Pacific small island developing states: Potential loss of benefits via human disturbance and climate change. (November 2020) - Brodie, Gilianne; Holland, Elisabeth; N'Yeurt, Antoine De Ramon; Soapi, Katy; Hills, Jeremy
Abstract: Seagrasses provide a wide range of services including food provision, water purification and coastal protection. Pacific small island developing states (PSIDS) have limited natural resources, challenging economies and a need for marine science research. Seagrasses occur in eleven PSIDS and nations are likely to benefit in different ways depending on habitat health, habitat cover and location, and species presence. Globally seagrass habitats are declining as a result of anthropogenic impacts including climate change and in PSIDS pressure on already stressed coastal ecosystems, will likely threaten seagrass survival particularly close to expanding urban settlements. Improved coastal and urban planning at local, national and regional scales is needed to reduce human impacts on vulnerable coastal areas. Research is required to generate knowledge-based solutions to support effective coastal management and protection of the existing seagrass habitats, including strenghened documentation the socio-economic and environmental services they provide. For PSIDS, protection of seagrass service benefits requires six priority actions: seagrass habitat mapping, regulation of coastal and upstream development, identification of specific threats at vulnerable locations, a critique of cost-effective restoration options, research devoted to seagrass studies and more explicit policy development.